A Study of Single Photon Emission Computed Tomography by using Geant4/GATE (Journal of Nuclear Technology in Applied Science, 2019)
The aim of this research is to validate and investigate the Geant4/GATE platform for the simulation of a dual-head detector SIEMENS Symbia E gamma camera installed in El-Kaser El-Ainy (Nuclear Medicine and Radiotherapy Unit) at Cairo University. Each camera consists of a lead collimator, scintillation crystal, and head shielding. The back compartment consists of photomultiplier tubes and electronic circuits behind the crystal. The photoelectric effect, Compton scattering, atomic ionization, bremsstrahlung, multiple scattering, and Rayleigh scattering are included in the simulated physics processes. The experimental data from the Quality Control measurements (Energy resolution, Uniformity, Spatial resolution and Sensitivity) versus the simulation results from GATE are compared.All The measurements are performed by using the radioisotope Tc-99m to determine the energy resolution and extrinsic sensitivity with a Low Energy High Resolution (LEHR) collimator and to ensure the quality of the scintillation crystal without collimator by measuring the uniformity. Other collimators are also used to estimate their extrinsic spatial resolutions and the corresponding extrinsic sensitivity values. In addition, a quadrant bar phantom consisting of 4 sets of lead bars in each quadrant is used to determine the Modulation Transfer Function (MTF) as a characteristic of the camera intrinsic spatial resolution.
Keywords: SPECT; Quality Control; Quadrant Bar Phantom; Monte Carlo; GATE